Choosing the most suitable NGS technology to combine with a standardized viral enrichment protocol for obtaining complete avian orthoreovirus genomes from metagenomic samples - Álvarez-Narváez, Sonsiray; Harrell, Telvin L.; Nour, Islam; Mohanty, Sujit K.; Conrad, Steven J. (Frontiers in Bioinformatics, 2025)
Since viruses are obligate intracellular pathogens, sequencing their genomes results in metagenomic data from both the virus and the host. Virology researchers are constantly seeking new, cost-effective strategies and bioinformatic pipelines for the retrieval of complete viral genomes from these metagenomic samples. Avian orthoreoviruses (ARVs) pose a significant and growing threat to the poultry industry and frequently cause economic losses associated with disease in production birds. Currently available commercial vaccines are ineffective against new ARV variants and ARV outbreaks are increasing worldwide, requiring whole genome sequencing (WGS) to characterize strains that evade vaccines. This study compares the effectiveness of long-read and short-read sequencing technologies for obtaining ARV complete genomes. We used eight clinical isolates of ARV, each previously processed using our published viral genome enrichment protocol. Additionally, we evaluate three assembly methods to determine which provided the most complete and reliable whole genomes: De novo, reference-guided or hybrid. The results suggest that our ARV genome enrichment protocol caused some fragmentation of the viral cDNA that impacted the length of the long reads (but not the short reads) and, as a result, caused a failure to produce complete genomes via de novo assembly. Overall, we observed that regardless of the sequencing technology, the best quality assemblies were generated by mapping quality-trimmed reads to a custom reference genome. The custom reference genomes were in turn constructed with the publicly available ARV genomic segments that shared the highest sequence similarity with the contigs from short-read de novo assemblies. Hence, we conclude that short-read sequencing is the most suitable technology to combine with our ARV genome enrichment protocol.